A special place for women ebook - Hankin, Laura (2021)
As seen on Good Morning America and The Late Show with Stephen Colbert “One of the smartest, sharpest, and funniest books I’ve read in years... Some books are meant to be devoured—this one does the devouring.”—Emily Henry, #1 New York Times bestselling author of People We Meet on Vacation One of Summer 2021's Most Anticipated Novels Good Morning America, Cosmopolitan , Good Housekeeping , Real Simple , theSkimm, E! Online, Oprah Daily, The New York Post , Woman's Day , Parade, Bustle, Yahoo!, The Stripe, Popsugar, Medium, Lithub, Book Riot, The Nerd Daily, and more! It’s a club like no other. Only the most important women receive an invitation. But one daring young reporter is about to infiltrate this female-run secret society, whose bewitching members are caught up in a dark and treacherous business. From the author of Happy and You Know It . For years, rumors have swirled about an exclusive, women-only social club where the elite tastemakers of NYC meet. People in the know whisper all sorts of claims: Membership dues cost $1,000 a month. Last time Rihanna was in town, she stopped by and got her aura read. The women even handpicked the city's first female mayor. But no one knows for sure.  That is, until journalist Jillian Beckley decides she's going to break into the club. With her career in freefall, Jillian needs a juicy scoop, and she has a personal interest in bringing these women down. But the deeper she gets into this new world—where billionaire "girlbosses" mingle with occult-obsessed Bohemians—the more Jillian learns that bad things happen to those who dare to question the club's motives or giggle at its outlandish rituals.   The select group of women who populate the club may be far more powerful than she ever imagined.  And far more dangerous too.